LEGAL ANALYSIS OF THE JU'ALAH CONTRACT FROM THE PERSPECTIVE OF AHKAM HADITH - Salma, Rahmani; Saran, Mohammad; Komaruddin, Koko (Tadayun: Jurnal Hukum Ekonomi Syariah, 2024)
The demands and dynamics of human life are becoming more complex due to technological advancements and economic progress. It is causing various contemporary issues in Islamic jurisprudence, such as affiliate marketing practices. Affiliate marketing, in terms of its technical execution, uses a Ju’alah scheme or contract. This study analyzes the quality and strength of Hadith, as reported by Bukhari number 5736, regarding Ruqyah with Surah Al-Fatihah as a legal foundation for Ju’alah in Islamic law. The study employs a qualitative and descriptive-analytical method based on Takhrij and Syarah hadith. This study's data was sourced from library research procedures, including primary and secondary data. The research elucidates that, from the perspective of Hadith, ju’alah represents a commitment to rewarding an effort completed by one party. The permissibility of ju’alah in Hadith Bukhari no.5736, shown through the response of Prophet Muhammad saw, thus approved Abu Sa'id al Khudri's acts during the execution of ruqyah and their agreement to give a goat as a reward/return for the ruqyah. According to the analysis result of Hadith Bukhari no. 5736 regarding ruqyah with Surah Al-Fatihah, this Hadith has the status of hadith ahad and shahih quality, thereby establishing its viability as a hujjah or legal foundation for ju’alah in Islamic law. AbstrakTuntutan dan dinamika dalam kehidupan manusia semakin kompleks, terutama akibat perkembangan teknologi dan kemajuan ekonomi, yang serta merta memunculkan berbagai isu kontemporer dalam fikih muamalah, seperti praktik pemasaran afiliasi. Pemasaran afiliasi dari teknis pelaksanaannya, menggunakan skema atau akad ju’alah. Penelitian ini mengkaji kualitas dan kekuatan hadis riwayat Bukhari no.5736 tentang ruqyah dengan surat al-fatihah sebagai landasan hukum akad ju’alah. Penelitian ini menerapkan pendekatan kualitatif melalui metode deskriptif-analitis yang bersumber dari metode takhrij hadis dan syarah hadis. Sumber data penelitian ini didasarkan pada pengumpulan data melalui studi kepustakaan (library research), yang mencakup sumber-sumber primer dan sekunder. Hasil penelitian menunjukkan bahwa dalam perspektif hadis, akad jua’alah merupakan komitmen pemberian imbalan sebagai balasan atas tugas atau pekerjaan yang telah dilakukan. Kebolehan akad ju’alah dalam hadis Riwayat bukhari no.5736 ditunjukkan melalui respon Nabi saw yang membenarkan tindakan Abu Sa’id al Khudri dalam melaksanakan ruqyah dan kesepakatan pemberian kambing sebagai imbalan atas ruqyah tersebut. Berdasarkan hasil analisis terhadap hadis Riwayat bukhari no.5736 tentang ruqyah dengan surat al-fatihah, dapat disimpulkan bahwa hadis berstatus hadis ahad dan berkualitas shahih, sehingga dapat dijadikan sebagai hujjah atau landasan hukum akad ju’alah.